A Semiotic Analysis In KFC Christmas Themed Advertisements - Ni Luh Vira Nitya Rini; Desak Putu Eka Pratiwi (RETORIKA: Jurnal Ilmu Bahasa, 2025)
In modern marketing, advertisements act not only as promotional tools but also as cultural texts rich in symbolic meaning. This study analyzes how KFC’s Christmas-themed advertisements employ semiotic signs to convey messages of warmth, celebration, and consumer engagement. Using a qualitative descriptive method with an observational approach, the research examines both verbal elements such as slogans and greetings and non-verbal components like imagery, color, and festive symbols. The analysis draws on Saussure’s (1983) theory of signifier and signified, Barthes’ (1972) concept of cultural myths, and Wierzbicka’s (1996) interpretations of color symbolism. Findings reveal that KFC effectively integrates textual and visual signs, including images of a fried chicken Christmas tree, red festive backgrounds, seasonal icons, and warm greetings to evoke emotional responses. These signs work together to associate the brand with traditional holiday values such as joy, togetherness, and generosity. By embedding its product within a culturally resonant and emotionally charged framework, KFC enhances the persuasive power of its advertisements. This study highlights the significance of analyzing both verbal and non-verbal elements to fully understand how meaning is constructed in advertising. It contributes to semiotic and marketing literature by illustrating how advertisements function as multidimensional texts that connect commercial aims with cultural narratives.